2004
DOI: 10.1111/j.1469-8137.2004.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of delayed fruit harvest on photosynthesis, transpiration and nutrient remobilization of apple leaves

Abstract: Summary• The aim of the work was to compare autumnal photosynthesis and remobilization processes in apple ( Malus domestica ) trees harvested either at commercial harvest date or 6 wk later (delayed harvest).• Apple leaf photosynthesis, measured by porometry, remained large at 8 -14 µmol CO 2 m − 2 s − 1 and was not limited by stomatal function after the commercial harvest date. The autumnal reduction both in photosynthesis and in vivo RUBISCO activity was less pronounced in apple trees with a delayed harvest.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 23 publications
1
23
0
1
Order By: Relevance
“…18 lmol CO 2 m -2 s -1 (Fig. 4), because apple leaf photosynthesis was saturated, with respect to light, at 800-1,000 lmol PAR m -2 s -1 (Ebert andCassiera 2000, Tartachnyk andBlanke 2004). Our result resembles those of Widmer (1997), Stampar et al (2002) and Romo-Chacon et al (2007), who obtained no significant differences in photosynthesis on a sunny day in Europe or high light conditions in Mexico, between trees with and without black or white hailnets.…”
Section: Leaf Photosynthesis Transpiration and Chlorophyll Contentmentioning
confidence: 97%
“…18 lmol CO 2 m -2 s -1 (Fig. 4), because apple leaf photosynthesis was saturated, with respect to light, at 800-1,000 lmol PAR m -2 s -1 (Ebert andCassiera 2000, Tartachnyk andBlanke 2004). Our result resembles those of Widmer (1997), Stampar et al (2002) and Romo-Chacon et al (2007), who obtained no significant differences in photosynthesis on a sunny day in Europe or high light conditions in Mexico, between trees with and without black or white hailnets.…”
Section: Leaf Photosynthesis Transpiration and Chlorophyll Contentmentioning
confidence: 97%
“…In a less productive and less vigorous apple genotype, Panzacchi et al (2012) have also found an average NPP value of 785 g C m −2 yr −1 . The presence of a large amount of fruit on an apple tree is known to enhance specific leaf photosynthesis as a consequence of their role as a sink, which allows for a more rapid download of photosynthates from the phloem with respect to apple trees not bearing fruit (Giuliani et al, 1997;Tartachnyk and Blanke, 2004).…”
Section: Magnitude Of C Fluxesmentioning
confidence: 99%
“…Currently available data show the capacity of plants to retain K by resorption. Diverse results have been reported in studies comparing the resorption efficiency (RE) for N, P and K. A number of different REs have been observed by researchers: N = P < K (van den Driessche, 1985;Nieminen & Helmisaari, 1996;Sardans et al, 2005), P < N = K (Ozbucak et al, 2008), N < K = P (Chuyong et al, 2000), N > K > P (Yin et al, 2009), P > K > N ( Salehi et al, 2013), K <N = P (Helmisaari, 1992;Duchesne et al, 2001;Tartachnyk & Blanke, 2004;Hagen-Thorn et al, 2006) and N = P = K (Gallardo et al, 1999;Trémolières et al, 1999). A recent review of a global dataset has observed that the RE for K on a global scale (70.1%) seems to be higher than the RE for N (62.1%) and P (64.9%) (Vergutz et al, 2012), although most of the studies reviewed by these authors did not take into account the role of leaf leaching when calculating RE.…”
mentioning
confidence: 99%